Evasive Entrepreneurship and Institutional Change - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2014)
In this paper, we argue that evasive entrepreneurship is an important source of innovation in the economy. Institutions may prevent or raise the cost of exploiting business opportunities, which can trigger evasive behavior because an entrepreneur may earn large rents by circumventing institutional impediments. Paradoxically, institutions may be less of a constraint for entrepreneurs than for other economic agents because entrepreneurs may be better able to evade them. Although evasive entrepreneurship can be both productive and unproductive/destructive, its dynamic character is more important because evasive entrepreneurship may be able to prevent economic development from being stifled by existing institutions during times of rapid economic change. Furthermore, if evasive entrepreneurship becomes sufficiently widespread and economically important, it may trigger a response from lawmakers and regulators, leading to institutional change with potentially important welfare implications. We illustrate this thesis by considering a number of real-word examples of evasive entrepreneurship.
Keywords: L50; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Regulation; Self-employment